It takes three to tango: An ethnography of triadic involvement of residents, families and nurses in long‐term dementia care - Luzan Koster; Henk Nies (Wiley, 2022)
Abstract Background Researchers often stress the necessity and challenge of integrating the positionings of residents, family members and nurses in order to realize each actor's involvement in long‐term dementia care. Yet most studies approach user and family involvement separately. Aim To explain how productive involvement in care provision is accomplished in triadic relationships between residents, family members and nurses. Methods An ethnographic study of identity work, conducted between 2014 and 2016 in a Dutch nursing home. Findings We identify four ideal‐typical identity positionings performed by nurses through daily activities. The findings reveal how their identity positionings were inseparable from those of the residents and family members as they formed triads. Congruent, or 'matching', identity positionings set the stage for productive involvement. Our systematic analysis of participants' identity work shows how-through embedded rights and responsibilities-their positionings inherently shaped and formed the triadic types and degrees of involvement observed within these relationships. Discussion and conclusion This study both unravels and juxtaposes the interrelatedness of, and differences between, the concepts of user and family involvement. Accordingly, our findings display how residents, family members and nurses-while continuously entangled in triadic relationships-can use their identity positionings to accomplish a variety of involvement activities. To mirror and optimize the implementation of user and family involvement, we propose a rights‐based and relational framework based on our findings. Patient or public contribution Conversations with and observations of residents; feedback session with the Clients' Council.